2014
DOI: 10.1111/jnc.12711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stimulation evokes rapid increases in extracellular adenosine concentration in the prefrontal cortex

Abstract: Mechanical perturbations can release ATP, which is broken down to adenosine. In this work, we used carbon-fiber microelectrodes and fast-scan cyclic voltammetry to measure mechanically-stimulated adenosine in the brain by lowering the electrode 50 μm. Mechanical stimulation evoked adenosine in vivo (average: 3.3 ± 0.6 μM) and in brain slices (average: 0.8 ± 0.1 μM) in the prefrontal cortex. The release was transient, lasting 18 ± 2 s. Lowering a 15 μm diameter glass pipette near the carbon-fiber microelectrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 47 publications
0
85
1
Order By: Relevance
“…Since its development, this modified waveform has been used to monitor adenosine dynamics in preparations as varied as murine spinal lamina (47, 48), brain slices (49, 50), and the striatum of anesthetized rats (51). Initial results have found that adenosine release is evoked by mechanical stimulation (52) and correlates to local O 2 fluctuations in intact tissue (51). More recently, researchers have developed a “sawhorse” waveform that holds at 1.35 V for 1 ms during the anodic scan (53).…”
Section: Electrochemical Detection Of New Neuromodulatorsmentioning
confidence: 99%
“…Since its development, this modified waveform has been used to monitor adenosine dynamics in preparations as varied as murine spinal lamina (47, 48), brain slices (49, 50), and the striatum of anesthetized rats (51). Initial results have found that adenosine release is evoked by mechanical stimulation (52) and correlates to local O 2 fluctuations in intact tissue (51). More recently, researchers have developed a “sawhorse” waveform that holds at 1.35 V for 1 ms during the anodic scan (53).…”
Section: Electrochemical Detection Of New Neuromodulatorsmentioning
confidence: 99%
“…Observing the real-time kinetics of in vivo neurochemical signaling is paramount to uncovering these functionalities and furthering our understanding of brain function and dysfunction. Electrochemical methods, such as fast scan cyclic voltammetry (FSCV) and chronoamperometry, have been widely employed for the sub second detection of electroactive neurochemicals such as dopamine (Jones et al 1995; Kawagoe et al 1992; Larsen et al 2011; Taylor et al 2013; Taylor et al 2015; Wightman et al 1988), ascorbic acid (Cofan and Radovan 2008; Yoshimi and Weitemier 2014), norepinephrine (Park et al 2011), adenosine (Nguyen et al 2014; Ross et al 2014) and serotonin (Hashemi et al 2012; Hashemi et al 2009; Hashemi et al 2011). The high temporal resolution afforded by these electrochemical detection techniques allows for in vivo concentration monitoring of neurochemicals on a physiologically relevant timescale (Robinson et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the first report on spontaneous adenosine transients has clearly demonstrated that the frequency of these spikes can be effectively modulated through A 1 receptors in the striatum of anesthetized rats. 13 Since several other analytes, including hydrogen peroxide and ATP, provide cyclic voltammograms with peaks around the same potential as adenosine, 17, 26 this demonstration can be considered as an important additional pharmacological verification for adenosine. Using the same pharmacological tool, cyclopentyladenosine (CPA), we explored how the activation of A 1 receptors affects the frequency and amplitude of striatal transients (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…29,30,31 The latest study by the Venton group revealed that momentary adenosine changes can transiently modulate phasic dopamine release via the A 1 receptor on the scale of seconds. 17 Therefore, a fast escalation in spontaneous adenosine efflux in some brain regions can be expected under the experimental conditions such as when the rat is exposed to noxious stimuli, which induces brief dopamine release. Figure 5 shows changes in spontaneous adenosine concentrations in the rat brain observed after administration of brief, 3 s tail pinches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation